2010
DOI: 10.1021/jp104141s
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Co-Phthalocyanine on Gold Investigated by Photoexcited Electron Spectroscopies: Indication of Co Ion−Metal Interaction

Abstract: The electronic properties of the interface between cobalt phthalocyanine and gold substrate were investigated by photoexcited electron spectroscopies (UPS, XPS, and XAES). The experimental data indicate a quite strong interaction between the organic molecules and the metallic substrate, which is concluded from the different shape of the XPS Co 2p and Co LVV Auger spectral lines, as well as a splitting of the HOMO in the UP spectra. Initial and final state effects in photoemission and a possible change of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
95
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 59 publications
(120 reference statements)
17
95
1
Order By: Relevance
“…For an interfacial charge transfer, an overlap of molecular orbitals of the organic with the metal is necessary, which was recently presumed for several organic interfaces. [23][24][25] In some cases such interactions result in the formation of gap states that can be directly observed in photoemission. [25] We note that differences in the energy-level alignment were recently observed between contaminated and clean metal surfaces.…”
Section: Energy-level Alignment At Electrodesmentioning
confidence: 99%
“…For an interfacial charge transfer, an overlap of molecular orbitals of the organic with the metal is necessary, which was recently presumed for several organic interfaces. [23][24][25] In some cases such interactions result in the formation of gap states that can be directly observed in photoemission. [25] We note that differences in the energy-level alignment were recently observed between contaminated and clean metal surfaces.…”
Section: Energy-level Alignment At Electrodesmentioning
confidence: 99%
“…226 Specifically, Co-phthalocyanines (CoPcs) are already applied in optoelectronic devices, gas sensors and they are considered a promising material for the development of low-dimensional organic molecular magnets. 227 Pcs are thermally and chemically stable 228 and their versatility plays an important role in material science and nanotechnology. 225 Thus, Pcs are usually studied and characterized by synchrotron radiation for probing different processes that occur at the atomic or the molecular level, as for example the charge transfer at the interface between a CoPc monolayer and Au.…”
Section: Discussionmentioning
confidence: 99%
“…225 Thus, Pcs are usually studied and characterized by synchrotron radiation for probing different processes that occur at the atomic or the molecular level, as for example the charge transfer at the interface between a CoPc monolayer and Au. 227 However, an important obstacle of these investigations delays in the radiation damage that can affect the electronic structure of molecules, making more difficult to achieve studies of these beam-sensitive materials. Some damages induced by radiation can be the break of the peptide bond between amino acids of a protein, a change in the 3d electron configuration of the transition metal center in a protein or a shift in the Fermi level due to the creation of defect states in the band gap of dye molecules.…”
Section: Discussionmentioning
confidence: 99%
“…29 Charge transfer between the substrate and the organic film has been reported for CoPc grown on Au films. [30][31][32][33] The charge transfer is limited to the first CoPc layers and consequently the overall effect is thickness dependent. In situ transistor field effect transport during CuPc film growth shows a decrease in the electron mobility as the layer thickness increases.…”
Section: Thickness Effectsmentioning
confidence: 99%
“…This strong dependence of the permittivity on CoPc thickness is in agreement with the previous works. [29][30][31][32][33][34] Previous studies demonstrated that the orientation of the CoPc molecules may vary with the thickness, changing from parallel to perpendicular to the substrate. 37 This effect strongly depends on the type of substrate and it will certainly affect to the dielectric properties and SPR curves of the CoPc films.…”
Section: Thickness Effectsmentioning
confidence: 99%